Arctic soil carbon turnover controlled by experimental snow addition, summer warming and shrub removal. (March 2020) - Ravn, Nynne R.; Elberling, Bo; Michelsen, Anders
Abstract: Northern latitude tundra heaths have accumulated large amounts of organic carbon (C) in the soil. Changes in climatic conditions such as temperature and winter precipitation might affect the C balance and potentially change these tundra ecosystems from being C sinks to sources of CO2 emitted to the atmosphere. However, studies on C fluxes with single and combined winter snow and summer warming effects are scarce. This study investigates gross ecosystem production (GEP), ecosystem respiration (ER), net ecosystem production (NEP) and carbon isotopic composition of CO2 emitted from a dry heath in arctic Greenland one and two years following field manipulations of summer temperature, shrub abundance and winter snow depth. Our aims were to quantify climatic change effects on CO2 fluxes and the growing season carbon balance of the ecosystem and to investigate shifts in δ 13 C of emitted CO2 potentially due changes in emission from old soil C versus recently fixed carbon. Ecosystem CO2 fluxes and δ 13 C-CO2 were measured using closed chambers, and soil CO2 concentrations and δ 13 C were measured depth-specifically using gas probes. We found a significant increase of CO2 emissions in all treatments during both years. Growing season NEP increased by 38 and 73% with 1 m enhanced winter snow depth, by 113 and 144% with summer warming and by 61 and 320% with total shrub removal in 2013 and 2014, respectively. The snow effect can be explained by the delay in the onset of growth as indicated by early season reduced vegetation greenness. The effect of warming was a result of an increase of ER by 39 and 32%, and the effect of shrub removal was mainly due to a reduction in GEP by 34 and 48%, in 2013 and 2014, respectively. Furthermore, the δ 13 C of the carbon source of CO2 emitted from warmed plots increased significantly two years after the experiment was initiated. This might indicate increased decomposition of 13 C enriched soil organic matter and hence increased mineralization of the old carbon stock in the soil under warmed conditions. The increase of NEP, the additive response of all treatments, and the indications of increased emission of carbon from old stocks due to warming (or warming-induced drying), demonstrate the risk of a relatively fast feedback to climate warming during the snow-free season. Graphical abstract: Image 1 Highlights: More snow, summer warming and shrub removal increase arctic tundra net CO2 emissions. Snow effect on carbon balance due to delayed leafing and low spring photosynthesis. Warming effect on carbon balance due to increased ER and unchanged GEP. Carbon isotope composition may indicate increased decomposition of old SOM by warming. Shrub removal effects on carbon balance mainly due to reduced photosynthesis.